Morphometric Analysis of Human Embryonic Stem Cell-Derived Ventricular Cardiomyocytes: Determining the Maturation State of a Population by Quantifying Parameters in Individual Cells - Harvey Y. S. Chan; Wendy Keung; Ronald A. Li; Andrew L. Miller; Sarah E. Webb (Hindawi Limited, 2015)
Quantitative methods were established to determine the level of maturation of human embryonic stem cell-derived ventricular cardiomyocytes (hESC-vCMs) that were treated with different metabolic stimulants (i.e., isoproterenol and oleic acid) during early differentiation. Cells were double-immunolabeled with α-actinin and COX IV antibodies, to label the myofibrils and mitochondria, respectively, after which images were acquired via confocal microscopy. In order to determine the extent of differentiation, image analysis protocols were then used to quantify cell shape and area, as well as the degree of myofibrillar organization and intercalation of mitochondria between the myofibrils within the cells. We demonstrated that oleic acid or isoproterenol alone, or a combination of the two, induced a more elongated hESC-vCM phenotype than the untreated controls. In addition, cells treated with isoproterenol alone exhibited a similar level of myofibrillar organization as the controls, but those treated with oleic acid with/without isoproterenol exhibited a more organized (parallel) orientation of myofibrils. The combined isoproterenol/oleic acid treatment also resulted in enhanced intercalation of mitochondria between the myofibrils. We suggest that these quantitative morphometric methods might serve as simple and effective tools that can be utilized in the determination of the level of structural maturation of hESC-vCMs.